Kanpur Confectionaries Private Limited (B ) - Dixit, Mukund R.; Dixit, Vandana (London : Indian Institute of Management, Ahmedabad, 2001)
This case study describes the developments in Kanpur Confectioneries Private Limited (KCPL) after the Gupta family decided to sign a contract with A-One Confectioneries Private Limited (APL) in December 1987.The case explains the technical and managerial processes that KCPL and APL adopted for learning, teaching and innovating in the company after signing the agreement. It also describes the diversification initiatives of the company and the new challenges it faced. Finally, the case also provides an opportunity for students in management education programs to analyse the linkages among the developments, evaluate the consequences and recommend directions for the future.
Originally published in Dixit, M., & Dixit, V. (2001). Kanpur Confectionaries Private Limited (B). BP0268(B) Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kanpur Confectionaries Private Limited -- Management -- Case studies; Family-owned business enterprises -- Management -- Case studies; Confectionery